The role of surgery after prolonged primary chemotherapy for advanced oesophageal adenocarcinoma. Issue 8 (17th August 2021) - Aboul‐Enein, Mohamed S.; Knight, William; Wulaningsih, Wahyu; Foley, Daniel M.; Dellaportas, Dionysios; Zylstra, Janine; Baker, Cara R.; Kelly, Mark; Smyth, Elizabeth; Lagergren, Jesper; Maisey, Nick; Allum, William H.; et al.
Abstract: Background: Most patients presenting with oesophageal cancer do so with advanced disease not suitable for surgery. However, there are examples of encouraging survival following surgery in highly selected patients who respond well to chemotherapy. Methods: This was a retrospective cohort study of patients who presented with advanced but nonvisceral metastatic oesophageal cancer. Consecutive patients on a prolonged primary chemotherapy pathway who underwent surgical resection following a favourable response to chemotherapy were included. Survival and recurrence rates were analysed using Cox regression, providing hazard ratios (HRs) with 95% confidence intervals (CIs). Results: A total of 57 patients included in the cohort operated between 2007 and 2015, the overall median survival was 44 months and the 5‐year survival was 42%. Prechemotherapy cN0/cN1 (HR: 0.27, 95% CI: 0.12–0.62) conferred an independent survival advantage compared to cN2 and cN3 disease. Poor differentiation (HR: 2.46, 95% CI: 1.11–5.42), R1 resection (HR: 2.43, 95% CI: 1.14–5.19) and advanced nodal status (HR: 3.28, 95% CI: 1.44–7.47) predicted worse survival on univariable analysis. Poor differentiation (HR: 3.93, 95% CI: 1.62–9.56) was independently associated with poor survival when adjusted for other variables. Conclusion: Patients who present with advanced inoperable oesophageal cancer who have a favourable response to chemotherapy represent a limited group of patients who may benefit from surgery.